The Influence of Organizational Culture and Principal Leadership Towards Teacher’s Performance - Prihatini, Deslina; Arafat, Yasir; Mulyadi, Mulyadi (Yayasan Sembilan Pemuda Indonesia, 2020)
This study determined the effect of organizational culture and principal leadership on teacher performance. This study uses quantitative methods with correlational research. The population of this study was 43 people, namely teachers of public elementary school teachers in Gugus 6, Gelumbang District. The data collection technique used a questionnaire. Data were analyzed using correlation analysis techniques and multiple linear regression. The results of this study indicate that: (1) organizational culture has a significant effect on the performance of Public Elementary School teachers in Gugus 6, Gelumbang District; (2) principal leadership has a significant effect on the performance of Public Elementary School teachers in Cluster 6, Gelumbang district, and (3) organizational culture and principal leadership simultaneously have a significant effect on the performance of public elementary school teachers in Gugus 6, Gelumbang District.